A new addition to the genus Apterolarnaca Gorochov, 2004 (Orthoptera: Gryllacrididae) - Bian, Xun; Lu, Xiangyi; Chen, Jiali (Zootaxa, 2021)
Herein one new species of Apterolarnaca is reported from Southwest China, Yunnan. The morphological features are described, and provided with colored charts of classification features. Up to now, the number of the genus reach four for Chinese fauna. The hootype is deposited in the Museum of Guangxi Normal University.